Advances in Quantum Mechanics - Bracken, Paul (IntechOpen, 2013)
The development of quantum mechanics has taken physics in a vastly new direction from that of classical physics from the very start. In fact, there continue at present to be many developments in the subject of a very fundamental nature, such as implications for the foundations of physics, physics of entanglement, geometric phases, gravity and cosmology and elementary particles as well. It is hoped the papers in this volume will provide a much needed resource for researchers with regard to current topics of research in this growing area.